Efficacy of horizontal jumping tasks as a method for talent identification of female rugby players - Agar-Newman, D. J.; Klimstra, M. D. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to explore the relationship between horizontal jumping tasks (standing long jump [SLJ] and standing triple jump [STJ]) and sprint speed (initial sprint speed [ISS] and maximum sprint speed [MSS]) in elite female rugby athletes. Data were collected from provincial, under 20 international fifteens players, in addition to senior sevens international level female rugby athletes (n = 114). Body weight, SLJ, STJ, 10-m sprint speed (ISS), 30- to 40-m sprint speed (MSS), initial sprint momentum, and maximal sprint momentum were analyzed. When categorized by horizontal jumping ability, there was a significant difference in sprint speeds (p < 0.001) between the top 50% and bottom 50% groups. Examining the relationship between horizontal jumping tasks and sprinting speed revealed a stronger correlation in the slowest 50% of athletes compared with the fastest 50%. A linear regression developed from STJ and body weight adequately predicted ISS (r = 0.645, p < 0.001) and MSS (r = 0.761, p < 0.001). In conclusion, horizontal jumping tasks can be used as a valuable performance test to identify differences of sprinting ability in elite female rugby players. However, the relationship between horizontal jumping tasks and sprinting speed seems to decrease in faster athletes. Further, STJ and body weight can be used to predict both ISS and MSS. Based on these data, it is suggested that only STJ be collected when identifying potential sprinting talent in female rugby athletes and caution be used when generalizing results across varying levels of athletes.